Effect of exercise combined with glucagon‐like peptide‐1 receptor agonist treatment on cardiac function: A randomized double‐blind placebo‐controlled clinical trial. Issue 7 (20th March 2017) - Jørgensen, Peter G.; Jensen, Magnus T.; Mensberg, Pernille; Storgaard, Heidi; Nyby, Signe; Jensen, Jan S.; Knop, Filip K.; Vilsbøll, Tina
Abstract : In patients with type 2 diabetes, both supervised exercise and treatment with the glucagon‐like peptide‐1 (GLP‐1) receptor agonist (GLP‐1RA) liraglutide may improve cardiac function. We evaluated cardiac function before and after 16 weeks of treatment with the GLP‐1RA liraglutide or placebo, combined with supervised exercise, in 33 dysregulated patients with type 2 diabetes on diet and/or metformin. Early diastolic myocardial tissue velocity was improved by exercise in the placebo group (mean ± standard deviation [s.d.] −7.1 ± 1.6 to −7.7 ± 1.8 cm/s, P   =  .01), but not in the liraglutide group (−7.1 ± 1.4 to −7.0 ± 1.4 cm/s, P  = .60; between groups, P   =  .02). Similarly, the mean ± s.d. ratio of early and atrial mitral annular tissue velocities improved in the placebo group (1.0 ± 0.4 to 1.2 ± 0.4, P  = .003), but not in the liraglutide group (1.0 ± 0.3 to 1.0 ± 0.3, P  = .87; between groups, P  = .03). We found no significant differences in heart rate, left ventricular (LV) structure or function within or between the groups. In conclusion, the addition of liraglutide to exercise in sedentary patients with dysregulated type 2 diabetes may blunt the suggested beneficial effect of exercise on LV diastolic function.